Methods for alleviation of impacts of axial diffusion on decomposition products monitoring in gas‐insulated transmission lines. (9th July 2021) - Qiu, Rui; Chen, Weijiang; Zhou, Wenjun; Liu, Ming; Zou, Jianming; Zheng, Yu; Li, Han; Hu, Shizhuo; Yu, Jianhui
Abstract: Considering the long length of gas‐insulated transmission lines (GILs), novel methods are required to alleviate the impacts of axial diffusion on decomposition products' monitoring. The diffusion process of two typical decomposition products, SO2 and SO2 F2, was studied. During the diffusion experiments, SO2 and SO2 F2 were generated by partial discharges. Based on Fick's law, an axial diffusion model of SO2 and SO2 F2 was proposed. By combining the experiment and simulation results, it was found that the diffusion coefficient of SO2 was greater than that of SO2 F2 . In addition, the concentration variation at different positions would experience some delay and decay in axial direction. The delay and decay were inversely related to the diffusion coefficient and increased with prolongation of the distance. Based on the diffusion characteristics determined, methods for optimising the monitoring positions, correcting concentration, and using the concentration ratio and generation rate were proposed to alleviate the impacts of diffusion. The methods could allow the decomposition products to be monitored in 1 month and reduce the monitoring error to 10% or less. The diffusion model and the methods could be useful for monitoring decomposition products in GILs.